Applications of In Vitro Tissue Culture Technologies in Breeding and Genetic Improvement of Wheat - Akila Wijerathna-Yapa; Vinita Ramtekey; Buddhini Ranawaka; Bhoja Raj Basnet (Plants, 2022)
Sources of new genetic variability have been limited to existing germplasm in the past. Wheat has been studied extensively for various agronomic traits located throughout the genome. The large size of the chromosomes and the ability of its polyploid genome to tolerate the addition or loss of chromosomes facilitated rapid progress in the early study of wheat genetics using cytogenetic techniques. At the same time, its large genome size has limited the progress in genetic characterization studies focused on diploid species, with a small genome and genetic engineering procedures already developed. Today, the genetic transformation and gene editing procedures offer attractive alternatives to conventional techniques for breeding wheat because they allow one or more of the genes to be introduced or altered into an elite cultivar without affecting its genetic background. Recently, significant advances have been made in regenerating various plant tissues, providing the essential basis for regenerating transgenic plants. In addition, Agrobacterium-mediated, biolistic, and in planta particle bombardment (iPB) gene delivery procedures have been developed for wheat transformation and advanced transgenic wheat development. As a result, several useful genes are now available that have been transferred or would be helpful to be transferred to wheat in addition to the current traditional effort to improve trait values, such as resistance to abiotic and biotic factors, grain quality, and plant architecture. Furthermore, the in planta genome editing method will significantly contribute to the social implementation of genome-edited crops to innovate the breeding pipeline and leverage unique climate adaptations.